Calculus : (Addison-Wesley, 1994)
The text itself is basically the same as "Calculus with Analytic Geometry" by Finney and Thomas. Professors Demana and Waits add their knowledge of graphing calculator technology and Mr. Kennedy adapts some of the information to be more relevant for the AP syllabus.